Type 2 Diabetes Mellitus. From the start – combination therapy - Francesco Indovina; Pierpaolo Falcetta; Stefano Del Prato (Сахарный диабет)
Modern treatment of T2DM requires a shift in paradigm with appropriate intensification of therapy from the very first time of diabetes diagnosis. This is supported by data showing how even a moderate delay in achieving good glycemic control can translate into a later increased risk of developing diabetic complications. The recognition of the complexity of the pathogenesis of T2DM leads to the appreciation of the importance of attacking the disease from different angles, i.e. simultaneous tackling of multiple mechanisms contributing to hyperglycemia. From the turn of century a growing number of new anti-hyperglycemic agents have been made available. As compared to the older ones, these new medicines have a more targeted mechanism of action as they act at the level of the specific pathophysiologic disturbances accounting the development and progression of hyperglycemia. Because of that drugs can be use in combination taking advantage of their complementary mechanisms of action and synergistic. If introduced earlier in the natural history of the disease combination therapy may contribute avoiding undesirable exposure to even mild chronic hyperglycemia and provide early benefits. With respect to that in this review we will discuss advantages, disadvantages and still unanswered questions related to the use of early combination therapy in type 2 diabetes.